Training of Trainers (TOT) bagi Para Instruktur Bahasa Korea di LPK (Lembaga Pelatihan Kerja) Bahasa Korea di Indonesia - Suray Agung Nugroho (Faculty of Cultural Sciences, 2019)
The community service (Pengabdian kepada Masyarakat/PkM) held in 2019 is a continuation of PkM which was carried out in 2018 on how LPK (Lembaga Pelatihan Kerja) instructors and students interpret the EPS TOPIK (Employment Permit System – Test of Proficiency in Korean Language). Based on the assessment of the ability and weaknesses of prospective PMI (Pekerja Migran Indonesia=Indonesian Migrant Workers) in understanding Korean, the Korean Language and Culture Program conducted the second PkM which was specifically intended for instructors at LPK through Training of Trainers (ToT). The ToT participants were 30 instructors, members of PELBAKORI (Association of Korean Language LPK in Indonesia). The material provided in this ToT were: (a) Important steps to mastering Korean vocabulary and grammar and (b) Points to ponder in understanding Korean culture.————————————————————–PkM yang dilakukan pada tahun 2019 ini adalah kelanjutan dari PkM yang dilaksanakan pada tahun 2018 tentang bagaimana instruktur LPK (Lembaga Pelatihan Kerja) dan peserta didik memaknai EPS TOPIK (Employment Permit System-Test of Proficiency in Korean Language). Berdasarkan asesmen kemampuan dan kelemahan para calon PMI (Pekerja Migran Indonesia) dalam memahami bahasa Korea yang telah diperoleh dalam kegiatan PkM tahap pertama, Prodi Bahasa dan Kebudayaan Korea merancang PkM kedua yang khusus ditujukan untuk para instruktur di LPK, yaitu Training of Trainers (ToT) bagi pengajar bahasa Korea di LPK-LPK Bahasa Korea. Peserta ToT berjumlah 30 instruktur di LPK penyelenggara kursus bahasa Korea yang tergabung dalam PELBAKORI (Perhimpunan LPK Bahasa Korea se-Indonesia). Materi yang diberikan dalam ToT ini adalah (a) langkah-langkah penting dalam menguasai tata bahasa dan kosakata bahasa Korea dan (b) pengetahuan sekitar budaya Korea.